2022
DOI: 10.1111/apa.16608
|View full text |Cite
|
Sign up to set email alerts
|

Functional constipation as a risk factor for pyelonephritis and recurrent urinary tract infection in children

Abstract: Urinary tract infection (UTI) is among the most common bacterial infections in childhood affecting up to 8.4% of girls and 1.7% of boys within the first 6 years of life. 1,2 Pyelonephritis is defined as an upper UTI involving the upper urinary tract and kidney parenchyma. This potentially serious condition can lead to renal scarring, 3,4 which can further result in loss of kidney function and long-term sequelae such as hypertension. 5 Approximately 85-95% of upper and lower UTIs are caused by Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…Many authors observed a positive correlation of BBD and rUTI [ 43 , 44 , 45 , 46 ]. Axelgaard et al found that constipation was positively associated with rUTI in children, particularly girls aged 4 to 18 years without CAKUT [ 47 ]. In our study group, we observed a similar dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors observed a positive correlation of BBD and rUTI [ 43 , 44 , 45 , 46 ]. Axelgaard et al found that constipation was positively associated with rUTI in children, particularly girls aged 4 to 18 years without CAKUT [ 47 ]. In our study group, we observed a similar dependence.…”
Section: Discussionmentioning
confidence: 99%
“…It impacts children, family members, caregivers, and medical professionals [11,31,138,139]. Reduced stool frequency causes fecal incontinence (FI) [140], anal fissures [141], recurrent urinary tract infections (RUTI) [142], and enuresis in children [143]. In individuals with severe constipation, stool became solid.…”
Section: Impact Of Constipationmentioning
confidence: 99%
“…Multiple research projects reported that pediatric patients with chronic constipation often concurrently suffer from RUTI and pyelonephritis. These patients frequently had diverse kidney and urinary tract anatomical abnormalities revealed through X-ray and ultrasonographic examination [142,151,152]. Longstanding constipation has the potential to alter the detrusor muscle activity of the urinary bladder and augment excitatory serotoninergic function, increasing the likelihood of enuresis or urine incontinence [143,[153][154][155][156].…”
Section: Impact Of Constipationmentioning
confidence: 99%